Functional Development of the Human Gastrointestinal Tract: Hormone- and Growth Factor-Mediated Regulatory Mechanisms - Daniel Ménard (Canadian Journal of Gastroenterology)
The present review focuses on the control of gastrointestinal (GI) tract development. The first section addresses the differences in general mechanisms of GI development in humans versus rodents, highlighting that morphogenesis of specific digestive organs and the differentiation of digestive epithelia occur not only at different stages of ontogeny but also at different rates. The second section provides an overview of studies from the author's laboratory at the Université de Sherbrooke pertaining to the development of the human fetal small intestine and colon. While both segments share similar morphological and functional characteristics, they are nevertheless modulated by distinct regulatory mechanisms. Using the organ culture approach, the author and colleagues were able to establish that hormones and growth factors, such as glucocorticoids, epidermal growth factor, insulin and keratinocyte growth factor, not only exert differential effects within these two segments, they can also trigger opposite responses in comparison with animal models. In the third section, emphasis is placed on the functional development of human fetal stomach and its various epithelial cell types; in particular, the glandular chief cells responsible for the synthesis and secretion of gastric enzymes such as pepsinogen-5 and gastric lipase. Bearing in mind that limitations of available cell models have, until now, greatly impeded the comprehension of molecular mechanisms regulating human gastric epithelial cell functions, the last section focuses on new human gastric epithelial cell models recently developed in the author's laboratory. These models comprise a novel primary culture system of human fetal gastric epithelium including, for the first time, functional chief cells, and human gastric epithelium cell lines cloned from the parental NCI-N87 strain. These new cells lines could serve important applications in the study of pathogenic action and epithelial regeneration.